EU Environmental Law in the Digital Age: A Critical Outlook on the Twin Transition’s Legal Structure - Aude-Solveig Epstein (European Journal of Risk Regulation)
The European Union (EU) has embraced the “twin transition” – the simultaneous pursuit of digitalisation and ecological transformation – as a cornerstone of its industrial policy. EU lawmakers argue that digital technologies can advance environmental protection by enhancing environmental monitoring, optimising resource use, and enabling data-driven sustainability efforts. However, this vision tends to overlook the environmental costs of digitalisation, including rising energy and water consumption, intensive resource extraction, and the proliferation of electronic waste. This article critically examines whether EU law is adequately equipped to support a twin transition, drawing on a black-letter analysis of EU legal provisions, as well as insights from science and technology studies and critical environmental law. It posits that, while environmental law plays a significant role in the datafication of the environment and the digitalisation of society, it falls short in regulating digital technology and data in ways that advance sustainability. For the twin transition to evolve beyond a political slogan and deliver real ecological benefits, substantial legal reforms would be required. The regulation of digital technology would have to move beyond corporate self-regulation and disclosure-based models of environmental governance. Data governance should be reoriented to emphasise freedom of access and a more deliberatively restrained approach to data generation.